1992
DOI: 10.1104/pp.98.3.1202
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Ca-ATPase of Radish Seedlings

Abstract: The effect of calmodulin on the activity of the plasma membrane Ca-ATPase was investigated on plasma membranes purified from radish (Raphanus satlvus L.) seedlings. Calmodulin stimulated the hydrolytic activity and the transport activity of the plasma membrane Ca-ATPase to comparable extents in a manner dependent on the free Ca2+ concentration. Stimulation was marked at low, nonsaturating Ca2 concentrations and decreased increasing Ca2+, so that the effect of calmodulin resulted in an increase of the apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…These data are consistent with the lack of a calmodulin binding domain in the deduced LCA amino acid sequence (Wimmers et al, 1992). In previous studies, calmodulin sensitivity was reported for the PM Ca2+-ATPases from maize (Robinson et al, 1988;Briars and Evans, 1989), red beet roots (Williams et al, 1990), carrot cell cultures (Hsieh et al, 1991), and radish seedlings (Rasi-Caldogno et al, 1992. In contrast, calmodulin had no effect on the PM Ca2+-ATPases from pea roots (Butcher and Evans, 1987) and Commelina communis leaves (Siebers et al, 1990).…”
Section: )supporting
confidence: 75%
“…These data are consistent with the lack of a calmodulin binding domain in the deduced LCA amino acid sequence (Wimmers et al, 1992). In previous studies, calmodulin sensitivity was reported for the PM Ca2+-ATPases from maize (Robinson et al, 1988;Briars and Evans, 1989), red beet roots (Williams et al, 1990), carrot cell cultures (Hsieh et al, 1991), and radish seedlings (Rasi-Caldogno et al, 1992. In contrast, calmodulin had no effect on the PM Ca2+-ATPases from pea roots (Butcher and Evans, 1987) and Commelina communis leaves (Siebers et al, 1990).…”
Section: )supporting
confidence: 75%
“…The pH sensitivity of the PM CaATPase affinity for Ca2", and thus of its activity at physiological Ca2+ concentrations, might constitute a linkage between Ca2" and pH homeostasis in the plant cell (2,12). These points will be discussed further in the accompanying paper with respect to the role of calmodulin in regulating the activity of the PM Ca-ATPase (19).…”
mentioning
confidence: 99%
“…In fact, it is half-saturated by Ca2+ in the micromolar range and has a very high affinity for MgATP (Rasi-Caldogno et al, 1989;Carnelli et al, 1992;De Michelis et al, 1992. Finally, the PM Ca2+-ATPase activity is regulated by CaM, which strongly increases the V,,, of the reaction, thus making the enzyme up-regulated by an increase of cytosolic Ca2+ and Ca2+-CaM concentrations (Malatialy et al, 1988;Robinson et al, 1988;Williams et al, 1990;Erdei and Matsumoto, 1991;Carnelli et al, 1992;Rasi-Caldogno et al, 1992;De Michelis et al, 1993).…”
mentioning
confidence: 99%